From farms to fuel tanks - Hiatt, Shon R.; Carlos, W. Chad (Strategic Management Journal, 2019)
[Research Summary: Although scholarship has demonstrated that market categories offer important signals to entrepreneurs about which goods and services are valued, little research has considered how entrepreneurs make sense of and exploit opportunities when contestation over category meaning persists. Using the emergent U.S. biodiesel market as a context, we present a framework to explain how the salience of different stakeholder frames shapes entrepreneurs' perceptions of market opportunities and influences their market-entry strategies. By showing how framing contests affect entrepreneurial outcomes, this study illuminates the underlying cognitive mechanisms that impact market meaning and offers important implications for the literatures on entrepreneurship, market-category evolution, framing contests, and grand challenges. Managerial Summary: Entrepreneurs entering new markets must consider how their products or services create value for customers. What customers value, however, is often shaped by competition between different stakeholders who seek to define problems and appropriate solutions. We argue and find that competing stakeholders influence what becomes valued in the market and shape the technologies and products developed by entrepreneurs. From the perspective of those promoting new markets, market growth requires a balancing act between maintaining control over market definitions and attracting new customers. In growing a new market, entrepreneurs and market pioneers may unintentionally attract other stakeholders who seek to alter or redefine market meanings, which can drive demand away from initial producers, foster the development and adoption of unforeseen technologies, and facilitate market entry of diverse organizations.]